Perbandingan Pengaruh Latihan Heel Raise dan Lunges Terhadap Peningkatan Power Tungkai - Muhammad Helmi Azzam; Sri Maryati; Ucu Abdul Ropi; Isna Daniyati Nursasih (Jurnal Keolahragaan, 2024)
The purpose of this study is: to determine whether there is a significant effect of heel raise and lunges exercises on increasing leg power in students who take extracurricular activities at SMK Kopri Bekasi. The research method used is a true-experimental design, the design used is "two group pretest-posttest design". The population of this study was 65 students of SMK Kopri Bekasi in grades XII A and E. The sample in this study was 28 male students of grades XII A and E of SMK Kopri Bekasi. The results of the calculation and significance test using a two-tailed average test, obtained a t-count of 1.21 which is smaller than the t-table = 1.71 at a confidence level of 0.95 with dk n1 + n2-2 = 26. The results of the calculation and significance test of the data on the increase in leg power from heel raise and lunges exercises showed no significant difference in increase, thus this can mean that both exercise groups are equally effective in increasing leg power in students who take extracurricular activities at SMK Kopri Bekasi.